Prehabilitation for Frail Patients Undergoing Colorectal Surgery: Lessons Learnt From a Randomised Feasibility Study - Furyk, Claire; Senthuran, Siva; Nye, Dia; Ho, Yik H.; Leicht, Anthony S. (Frontiers in Rehabilitation Sciences, 2021)
There is substantial interest by clinicians to improve the health outcomes of older and frail patients following major surgery, with prehabilitation a potential and important component of future standard patient care. We studied the feasibility of a randomised controlled trial of pre-operative prehabilitation in frail patients scheduled for colorectal surgery in regional Australia. We conducted a single blind, parallel arm, randomized controlled trial in a regional referral centre where colorectal surgical patients aged over 50 were invited to participate and screened for frailty. Frail patients were randomised to undertake either a four-week supervised exercise program with dietary advice, or usual care. The primary outcome was six-minute-walk-distance at baseline, pre-surgery (four weeks later) and at follow-up (four-six weeks post-operation). Secondary outcomes included physical activity level, health-related quality of life, and postsurgical complications. Feasibility outcomes were numbers of patients reaching each stage and barriers or reasons for withdrawal. Of 106 patients eligible for screening during the two-year study period, only five were able to be randomised, of which one alone completed the entire study to follow-up. Fewer patients than expected met the frailty criteria (23.6%), and many (22.6%) were offered surgery in a shorter timeframe than the required four weeks. Physical and psychological aspects of frailty and logistical issues were key for patients declining study participation and/or not complying with the intervention and/or all outcome assessments. Feasibility for a large randomised controlled trial of prehabilitation for frail colorectal patients was poor (~5%) for our regional location. Addressing barriers, examination of a large, dense population base and utilization of a frailty-screening tool validated in surgical patients are necessary for future studies to identify the impact of prehabilitation for frail patients.